Mistakes of diagnostics, conducting and treatments of the patients with bronchial asthma - N. A. Karoly; A. P. Rebrov (Бюллетень сибирской медицины, 2002)
On the basis of diagnostics of 100 patients, 25 doctors of Saratov and 72 histories of illness of the patients with severe acute asthma in four different hospitals there were presented the results that prove the great amount of defections in diagnostics quality, conducting and treatment of patients at various stages of rendering of medical aid. There were defined the difficulties of diagnostics and the main factor of severe current of asthma and death. The difficulties are both in absence of primary training of the patients, and in absence of constant, regular supervision of these patients by the local doctor. It is connected not only with the absence of time on doctor’s dialogue with the patient, but also with ignorance and frequently unwillingness of the doctor to learn the modern approaches of conducting and treatment of asthma. The received data confirms that the major factors conducting to increase of severe current of asthma and the increase of mortality are bad diagnostics, inadequate conducting and treatment, and the education of the patients is very necessary part of the general common program of asthma treatment.